Determinism of Temporal Variability in Size at Maturation of Sardine Sardina pilchardus in the Bay of Biscay - Véron, Matthieu; Duhamel, Erwan; Bertignac, Michel; Pawlowski, Lionel; Huret, Martin; Baulier, Loïc (Frontiers in Marine Science, 2020)
Age and size at maturation appear as key parameters governing the dynamics of a population as they affect growth rate, fecundity and survival. The expression of such life history traits is determined by genetic make-up and modulated by environmental factors mainly through phenotypic plasticity. Moreover, fishing, besides decreasing population size and changing demographic composition can alter allelic frequencies through fisheries-induced evolution by selecting for some particular traits. In the Bay of Biscay, a decreasing trend in both sardine body condition and size-at-age has recently been pointed out at the population level. The Probabilistic Maturation Reaction Norm (PMRN) approach was applied to help disentangle phenotypic plasticity and genetic changes. Based on the analysis of sardine spawning seasonality, PMRN was estimated by considering body condition as additional life-history state variable to predict the onset of maturation. The resulting PMRN was then used to investigate temporal trends in reaction norm midpoints to test whether changes in length at maturation can be explained by plastic and/or evolutionary adaptive change. Overall, our results emphasize for the first time that including sardine body condition as explanatory variable improves predictions of maturation probability. We found that better individual condition increases maturation probability. The assessment of temporal changes in length at maturation confirms the low plasticity in this trait for a species maturing mostly at age-1 and advocates for the use of a monthly time scale when investigating PMRNs for this species. Beside environmental variables included in this analysis (water temperature, chlorophyll-a and population biomass) that only show a weak correlation with PMRN midpoints, our results reveal no evidence for recent fisheries-induced evolution in the sardine stock of the Bay of Biscay. They suggest that the short-term variability in length at maturation is strongly dependent upon individual growth which is likely driven by environmental factors. For sardine fisheries management, our study highlights the need to consider both the length-composition data and the seasonality within a stock assessment model. Finally, we discuss the fact that considering individual growth trajectories should improve our understanding of the relationship between environmental variability and changes in maturation for sardine.